The effect of attitude, subjective normal and behavioral control on the intention to purchase intentions of processed noodles managed by non-muslim chinese ethnics in the city of Lhokseumawe - S Sumantri; R Rahmaniar; Mohd. Heikal (Management Research and Behavior Journal, 2022)
This study examined and analyzed the influence of attitudes, subjective norms, and behavioral control on the intention to purchase processed noodle foods managed by non-Muslim Chinese ethnicities in Lhokseumawe City. The research sample was 100 respondents who were consumers of Kak Acuh/Lisa Restaurant, Budi Resto & Caffe, Mamamia, and Kota Intan. The dependent variable used was purchase intention, and the independent variables were Attitude, Subjective Norm, and Behavioral Control. This study used multiple linear regression analysis tools. Hypothesis testing using the f-test found that Attitude, Subjective Norm, and Behavioral Control significantly influence Purchase Intention. Meanwhile, the t-test partially stated that Attitude, Subjective Norm, and Behavioral Control positively and significantly Purchase Intention.